1940
DOI: 10.1111/j.1939-0025.1940.tb05664.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of sitting, standing and walking of children reared with optimal pediatric care.

Abstract: HIS investigation represents a study of the beginning ages of sitting, stand-T ing and walking for a group of 349 infants reared with a relatively optimal degree of pediatric and home care. Age values in terms of central and deviational tehdencies are presented (Table I), our results are analyzed for sex differences (Tables I1 and 111), and intercorrelations of sitting, standing and walking data are determined (Table IV). Our results are compared with those of Shirley and the norms of Strang (Table V) and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1943
1943
1969
1969

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…5 months for sitting unsupported. Peatman and Higgons (1940) give medians for the last two milestones of 13 -3 and 6.7 months respectively, based on 73 children followed longitudinally by personal observation in a single paediatric private practice.…”
Section: Resultsmentioning
confidence: 99%
“…5 months for sitting unsupported. Peatman and Higgons (1940) give medians for the last two milestones of 13 -3 and 6.7 months respectively, based on 73 children followed longitudinally by personal observation in a single paediatric private practice.…”
Section: Resultsmentioning
confidence: 99%
“…Peatman and Higgons, in two reports (80,81), concluded from a study of 349 infants reared under conditions of relatively optimum pediatric and home care, that general health status had little, if anything, to do with the beginnings of sitting, standing, or walking. They further reported that weight and height of infants had no measurable effects on the development of these motor functions.…”
Section: Effects Of Physical Status and Health On Motor Developmentmentioning
confidence: 99%
“…Peatman and Higgons, in two reports (67,68), concluded from a study of 349 infants reared under conditions of relatively optimum pediatric and home care, that general health status had little, if anything, to do with the beginnings of sitting, standing, or walking. They further reported that weight and height of infants had no measurable effects on the development of these motor functions.…”
Section: Effects Of Physical Status and Health On Motor Developmentmentioning
confidence: 99%